The contribution of Eu3+ doping concentration on the modulation of morphology and luminescence properties of InVO4:Eu3+. Issue 56 (12th September 2018) - Li, Yinyan; Xu, Shiqing
Abstract : Nanomaterials of InVO4 and InVO4 :Eu 3+ were synthesized, and their morphology and luminescent properties could be modulated by Eu 3+ ion doping concentration. Abstract : Nanostructures of InVO4 and InVO4 :Eu 3+ were synthesized through a hydrothermal method with a post annealing process. The morphology and luminescence properties of InVO4 : x Eu 3+ can be modulated by Eu 3+ ion doping concentration. SEM and (HR)TEM studies indicated that different sizes of nanoparticles were obtained when the Eu 3+ ion concentration ranged from 2 mol% to 30 mol%, and middle-concave nanodisks or nanoparticles with different sizes were obtained with the Eu 3+ ion concentration ranging from 35 mol% to 45 mol%. Luminescence property studies indicated that the photoluminescence emission originated both from VO4 3− and Eu 3+, and the emission of VO4 3− was blue shifted, affected by the doped Eu 3+ ions. The CIE chromaticity diagram of Eu 3+ -doped indium vanadate exhibited green, blue-green, red, giving especially white light emission.